The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1371/journal.pone.0137875
|View full text |Cite
|
Sign up to set email alerts
|

Differential Relevance of NF-κB and JNK in the Pathophysiology of Hemorrhage/Resususcitation-Induced Liver Injury after Chronic Ethanol Feeding

Abstract: BackgroundChronic ethanol (EtOH) abuse worsens pathophysiological derangements after hemorrhagic shock and resuscitation (H/R) that induce hepatic injury and strong inflammatory changes via JNK and NF-κB activation. Inhibiting JNK with a cell-penetrating, protease-resistant peptide D-JNKI-1 after H/R in mice with healthy livers ameliorated these effects. Here, we studied if JNK inhibition by D-JNKI-1 in chronically EtOH-fed mice after hemorrhagic shock prior to the onset of resuscitation also confers protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Activation of stress-response kinase JNK, a member of the important MAPK family, is a common feature of alcohol-caused tissue injury ( 20 , 21 ). Other MAPK family members (p38 and extracellular ERK) may also contribute in a cellular context and type-dependent fashion ( 35 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of stress-response kinase JNK, a member of the important MAPK family, is a common feature of alcohol-caused tissue injury ( 20 , 21 ). Other MAPK family members (p38 and extracellular ERK) may also contribute in a cellular context and type-dependent fashion ( 35 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stress-activated c-Jun NH( 2 )-terminal kinase (JNK) is activated by many types of stress stimuli such as cardiovascular diseases, aging, and diabetes ( 16 19 ). JNK activation is well known to contribute to alcohol-caused organ damage ( 20 , 21 ). We recently reported that JNK activation promotes AF in aged hearts ( 18 , 19 ).…”
mentioning
confidence: 99%
“…Several studies in vitro, as well as in vivo, proved that JNK inhibitions with D-JNKI1 can offer an intriguing strategy against brain diseases, including excitotoxicity and cerebral ischemia [ 63 ], neuropathic pain [ 138 ], AD [ 139 , 140 ], SMA [ 141 ], deafness [ 142 , 143 ], ocular inflammation [ 144 ], liver injury [ 145 ], spinal cord injury [ 146 ] and traumatic brain injury [ 147 , 148 ]. The disadvantages of using a CPP, which is able to cross all the barriers (BBB) and inhibit all JNK isoforms in the whole body, are the possible side effects.…”
Section: Tuning Jnk3 Pathway By Using Jip-1 and β-Arrestin-2mentioning
confidence: 99%
“…The levels of ALT and AST in the serum are considered as a biochemical marker for assessing liver function [26], which were examined to explore effect of AC on hepatic function. Compared to unexercised mice, 60 min swimming failed to influence the levels of ALT and AST in serum ( P > 0.05, F = 0.18–1; Figure 3).…”
Section: Resultsmentioning
confidence: 99%